Targeted Interventions to Advance a Culture of Inquiry at a Large, Multicampus Hospital Among Nurses. (January 2018) - Carter, Eileen J.; Rivera, Reynaldo R.; Gallagher, Kelly A.; Cato, Kenrick D.
Abstract : OBJECTIVES: The aim of this study is to assist nurse leaders in developing innovative structures to foster a culture of inquiry among professional nurses. BACKGROUND: Critical to nurse's engagement in evidence-based practice (EBP) is a culture of inquiry, in which nurses critically evaluate patient care activities and actively review existing evidence to address identified clinical issues. A bundle of structural interventions was implemented across a large, multisite hospital to advance a culture of inquiry. We measured the impact of these interventions on nurses' library use and on nurses' knowledge, attitudes, and practices towards EBP. METHODS: Structural interventions included: 1) EBP and Research Committee meetings, in which nurses were educated on how to formulate a clinical question and critically appraise a research article; 2) Academic Partners Program, in which nurse academicians provided scholarly mentorship and guidance during monthly committee meetings; 3) hiring of clinical nurse scientists who provided 1-on-1 education and mentorship to clinical nurses in EBP and research; and 4) a Nurse Residency Program partnership, in which newly graduated nurses were required to complete an EBP project. We examined the impact of these structural interventions on nurses' use of library resources and nurses' knowledge, attitudes, and practices toward EBP. RESULTS: The implementation of structural interventions to support nurses' engagement in EBP was associated with a significant increase in the number of nurse-generated library consultative requests over time. Results showed high levels of nurse knowledge, attitudes, and practices in EBP. CONCLUSIONS: Nurse leaders may advance a culture of inquiry by providing the infrastructure to support EBP activities and by empowering nurses to question and seek answer to identified practice questions. Infrastructures should include access to scientific articles and partnerships with schools of nursing. Additional research is needed to validate nurse library use as a measure of nurse engagement in EBP.